Sports specialization in young athletes Evidence-based recommendations - Jayanthi, N.; Pinkham, C.; Dugas, L.; Patrick, B.; LaBella, C. (Sports Health: A Multidisciplinary Approach, 2012)
Sports specialization is intense training in 1 sport while excluding others. Sports specialization in early to middle childhood has become increasingly common. While most experts agree that some degree of sports specialization is necessary to achieve elite levels, there is some debate as to whether such intense practice time must begin during early childhood and to the exclusion of other sports to maximize potential for success. There is a concern that sports specialization before adolescence may be deleterious to a young athlete.